Do cartel breakdowns induce mergers? Evidence from EC cartel cases - Kai Hüschelrath; Florian Smuda (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We investigate the impact of cartel breakdowns on merger activity. Merging information on cartel cases decided by the European Commission (EC) between 2000 and 2011 with a detailed data set of worldwide merger activity, we find that, first, the average number of all merger transactions increase by up to 51 percent when comparing the three years before the cartel breakdowns with the three years afterwards. Second, for the subset of horizontal mergers, merger activity is found to increase even more - by up to 83 percent - after the cartel breakdowns. Our results not only suggest that competition authorities should consider mergers as potential 'second-best' alternative to cartels but also imply that resource (re)allocations in competition authorities, law practices and economic consultancies may become necessary to handle the increase in merger cases.
Keywords: L41; K21; 330; antitrust policy; cartels; mergers; cartel breakdown; European Union